PROAPOPTOTIC, ANTI-CELL PROLIFERATIVE, ANTI-INFLAMMATORY AND ANTI-ANGIOGENIC POTENTIAL OF CARNOSIC ACID DURING 7,12 DIMETHYLBENZ[A]ANTHRACENE-INDUCED HAMSTER BUCCAL POUCH CARCINOGENESIS. - Rajasekaran, Duraisamy; Manoharan, Shanmugam; Silvan, Simon; Vasudevan, Krishnamoorthy; Baskaran, Nagarethinam; Palanimuthu, Duraisamy (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The present study has investigated the modulating effect of carnosic acid on the expression pattern of cell proliferative (proliferating cell nuclear antigen (PCNA) cyclin D1 and a transcription factor c-fos), apoptotic (p53, Bcl-2, Bax caspase -3 and 9), inflammatory (Nuclear factor kappa B (NFκB) and cyclooxygenase-2 (COX- 2) and angiogenic (vascular endothelial growth factor (VEGF) markers during 7,12-dimethylbenz[a]anthracene (DMBA)-induced hamster buccal pouch carcinogenesis. Oral tumors were developed in the hamsters buccal pouches by painting with 0.5% DMBA in liquid paraffin three times a week for 14 weeks. Hundred per cent tumour formation (well-differentiated squamous cell carcinoma) accompanied by deregulation in the above mentioned molecular markers was noticed in hamsters treated with DMBA alone (tumour bearing hamsters). Oral administration of carnosic acid at dose of 10mg/kg bw to hamsters treated with DMBA not only completely prevented the tumour formation, but also corrected the abnormalities in the expression pattern of molecular markers. The present study suggests that carnosic acid might have inhibited the tumour formation by exerting anti-cell-proliferative, anti-inflammatory, anti-angiogenic and apoptotic potential during DMBA-induced hamster buccal pouch carcinogenesis.